Role of Triple D Score in Eswl: Our Experience at Urology Department Chandka Medical College Hospital Larkana Pakistan - Khob Chand Rohra, Aamir Ali Shaikh, Imran Khan, Safiullah Sohu, Hameed-Ur-Rehman Bozdar, Nisar Ahmed Shaikh, Amanullah Abassi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To detect usefulness of triple D score in ESWL (extracorporeal shock wave lithotripsy) for management of renal stone. Methodology: Retrospective Study was conducted at Urology department, CMCTH) at SMBBMedical University Larkana. 50 patients underwent ESWL from 2018 to 2020. All the related data were taken as well as demographic details, history and risk factor from the patients. Routine investigation carried out including Blood CP ESR, Urine DR, Blood sugar, Renal profile, urine culture sensitivity and CT KUB. The stone density, skin-to-stone distance, and stone size were calculated by a radiologist. Results: ESWL was performed on 50 patients with average age of 30± 8 years and a sex ratio (male female) of 1:0.3. The stone-free percentage after the first treatment session was 40 percent and 90 percent on 2nd sitting, based on the triple D score, which included stone size, skin to stone distance, and stone density (HU). The mean stone size was 15.8 mm, the Skin to Stone Distance was 6.4 cm, and the stone density was 594 HU were established respectively. Conclusion: The Triple D Score is easy to compute and reported by radiologist. The use of the Triple D Score in ESWL patients has been shown to improve overall ESWL success rates. Keywords: Extracorporeal, Shock, Wave, Lithotripsy, Renal stone and Triple D score